Perbandingan variasi tipe sudu dan tinggi impeller dengan jumlah sudu 9 buah terhadap daya dan efisiensi pada turbin vortex - Renhard Januard Sitindaon; Rafil Arizona (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
The lack of maximum use of alternative energy, especially water energy, so this research will be carried out with water turbines, namely vortex turbines. This turbine utilizes a water vortex to drive the blade and can operate at a relatively low head. This study aims to determine the effect of blade type on the power and efficiency of a more optimal turbine and get the best analysis results on the comparison of straight and curved blade type impellers on the power and efficiency of a 205 mm, 210 mm, and 215 mm high impeller vortex turbine with a total of 9 blades. The method used in this research is literature study, preparation of tools and materials, data collection then data processing and analysis. The results of this study compared to the straight blade impeller, the curved blade impeller gets the highest value of turbine power and efficiency. more details the curved blade impeller with a height of 215 mm and the number of blades of 9 pieces produces the highest turbine performance in this study. The resulting turbine power (Pt) is 46.77 watt and the resulting turbine efficiency (ht) is 13.41%. While in the straight blade type impeller the turbine power and efficiency results are lower than the curved blade type impeller. Especially the 205 mm straight blade impeller with 8 blades has the lowest power and efficiency results.